EMDR treatment for people with intellectual disabilities: a systematic review about difficulties and adaptations - Schipper-Eindhoven, Simone M.; de Knegt, Nanda C.; Mevissen, Liesbeth; van Loon, Jos; de Vries, Ralph; Zhuniq, Majlinda; Bekker, Marrie H. J. (Frontiers in Psychiatry, 2024)
Introduction: People with intellectual disabilities (ID) are at increased risk for developing Post Traumatic Stress Disorder (PTSD). Emerging evidence indicates that Eye Movement Desensitization and Reprocessing (EMDR) therapy is feasible and potentially effective for this group. However, communication, cognition, stress regulation, and attachment difficulties may interfere with the EMDR process. Adaptation of the EMDR protocol seems therefore required for this population. Aim: This review aims to systematically identify and categorize the difficulties in applying EMDR to people with ID and the adaptations made by therapists to overcome these challenges. Method: A literature search was performed in May 2023. Article selection was based on inclusion and exclusion criteria and quality appraisal. Results: After screening,13 articles remained for further review. The identified difficulties and adaptations were categorized into the three domains of adaptive functioning (i.e., conceptual, social, and practical functioning). Considerable difficulties in applying the EMDR protocol for this group were reported. The adaptations made by therapists to overcome these difficulties were highly variable. They could be divided into three main categories: adaptions in EMDR delivery (e.g., tuning to the developmental level of the client, simplifying language, decreasing pace), involvement of others (e.g., involving family or support staff during or in between sessions), and the therapeutic relationship (e.g., taking more time, supportive attitude). Discussion: The variability of the number of mentioned difficulties and adaptations per study seems to be partly related to the specific EMDR protocol that was used. In particular, when the Shapiro adult protocol was administered, relatively more detailed difficulties and adaptations were described than in publications based on derived existing versions of an EMDR protocol for children and adolescents. A probable explanation is that already embedded modifications in these protocols facilitate the needed attunement to the client's level of functioning. Practical implications: The authors of this review suggest that EMDR protocols for children and adolescents could be adapted for people with an intellectual disability. Further research should focus on the involvement of trusted others in EMDR therapy for people with ID and the therapeutic relationship from an attachment and relational-based perspective.